Prevalence and Patterns of Coronary Artery Anomalies in a Tertiary Cardiac Center of Nepal: A Coronary Angiographic Study - Poudel, Chandra M; Shakya, Smriti; Gajurel, Ratna M; Shrestha, Hemant; Devkota, Surya; Manandhar, Bhawani; Thapaq, Sanjeev; Khanal, Rajaram; Sharma, Manju; Yadav, Vijay (Journal of Institute of Medicine Nepal, 2022)
Introduction: The prevalence of coronary artery anomalies (CAAs), though rare, is nonetheless globally found in 0.2% to 1.3% of patients undergoing coronary angiography (CAG). We aimed to investigate the prevalence and patterns of CAAs. Methods: The data was collected retrospectively by analyzing the coronary angiographic data of 6000 consecutive adult patients undergoing coronary angiography between January 2016 to December 2020 at the Manmohan Cardiothoracic Vascular and Transplant Center. Results: Among 6000 patients, 89 (1.4%) had CAAs, with anomalies in the right coronary artery (RCA) being the most common (73%). The presence of a dominant RCA was found in 48 (53.9%) patients. The anomalous origin of RCA arising from the left sinus of valsalva was present in 33 (37.1%) patients. The left main (LM) anomaly was present in 49 (55%) patients with absent LM in 29 (32.6%) and a short LM in 20 (22.5%) patients, respectively. The left anterior descending (LAD) artery anomalies were present in 42 (47.2%) patients - out of which 29 (32.6%) had a separate origin of LAD from the left coronary sinus and 13 (14.6%) had a dual LAD. The left circumflex artery (LCx) anomalies were evident in 32 (35.9%) patients including separate origin from left coronary sinus in 29 (32.6%) and anomalous origin from the right coronary sinus in 3 (3.4%) patients, respectively. Two patients (2.2%) had coronary artery fistulas, both arising from LAD. Conclusion: Though rare, our study did discover the prevalence of CAAs to be1.4%.